Gastric Collision Tumors: An Insight into Their Origin and Clinical Significance. (12th February 2015) - Michalinos, Adamantios; Constantinidou, Anastasia; Kontos, Michael
Abstract : Collision tumors are rare neoplasms displaying two distinct cell populations developing in juxtaposition to one another without areas of intermingling. They are rare entities with only 63 cases described in English literature. Tumors encountered are gastric adenocarcinomas colliding with lymphomas, gastrointestinal stromal tumors, squamous cell carcinomas, and neuroendocrine tumors. Their cell origin is obsolete by the time of diagnosis. Different tumorigenesis theories have been suggested to explain their behavior, yet none has managed to provide satisfactory explanation for all cases. Clinically they are indistinguishable from the dominant tumor. Lack of data does not allow detailed assessment of their behavior yet they seem aggressive neoplasms with dismal prognosis. The majority of cases have been diagnosed postoperatively during histologic examination of specimens. There are no guidelines or concrete evidence to support best way of adjuvant or other types of treatment. However, these rare neoplasms might help in unlocking secrets of cancer behavior including tumorigenesis, differentiation, and adhesion and thus clinicians should be aware of their existence.